Data Distribution for Multiple Receivers in a Connected Car Environment Using 5G Communication. (12th June 2021) - Kim, Won-Bin; Seo, Daehee; Kim, Donghyun; Lee, Im-Yeong
Abstract : The development of communication technology has brought changes to various environments. The evolution from 3G to 4G Long-Term Evolution (LTE) was mainly aimed at improving communication speed. However, the evolution from 4G LTE to 5G New Radio (NR) is not aimed at improving speed alone. In addition to the existing communication types, 5G aims to improve communication to support the Internet of Things (IoT), media, and complex content to which things are connected. In such environments, point-to-point communication has a very inefficient structure to allow content providers to transmit data to many content users. In the 5G era, content providers must distribute content to numerous users, and in this process, they need to protect the content. Multireceiver encryption (MRE) is an encryption technology developed for this purpose. MRE allows multiple recipients to decrypt data using their own private key with single encryption of a data provider. With this technology, even if the number of data recipients is 100, 000 or 1, 000, 000, data can be distributed with single encryption. Therefore, while using the existing 1 : 1 encryption method, it is possible to solve the problem of inefficiency in performing encryption for each recipient. However, existing proposed MREs can cause key escrow problems and partial key verification problems. Furthermore, the privacy issues identifying the recipient may arise because anonymity is not available to the recipient. In addition, it is necessary to ensure a fair decryption process for all recipients which a legitimate user cannot decrypt. In this study, we attempted to address these problems, and through our model, it is possible to distribute the data more securely and efficiently in a 5G environment.